IMPLEMENTASI KARAKTER TOLERANSI DALAM MENGATASI BULLYING DI MADRASAH IBTIDAIYAH - Farabi, Reza Al; Fitriyani, Feny Nida; Muttaqin, Muhammad Fauzan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of tolerance character in overcoming bullying in Madrasah Ibtidaiyah. This study uses a qualitative approach with a case study method. The subjects of the study included students, teachers, and the head of the madrasah at MI Lantaburo Tangerang. Data collection was carried out through interviews, observations, and documentation. To ensure the validity of the data, triangulation techniques of sources and methods were used. Data analysis was carried out descriptively with the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of tolerance character is carried out through integration in learning, extracurricular activities, and school programs based on religious values. Teachers play an active role as role models and facilitators in building an attitude of mutual respect among students. In addition, it was found that a personal approach and parental involvement contributed to reducing the number of bullying in schools. The implications of this study indicate that tolerance character education can be an effective strategy in creating a harmonious school environment, thereby supporting the positive moral development of students.